Endurance evaluation of apple rootstocks for fe deficiencyinduced chlorosis through iron hunger and bicarbonate stress - Shahnam Ashtari; Mohammadreza Dadpour; Shahin Oustan; Fariborz Zaree Nahandi (علوم محیطی)
Introduction: Nowadays, the use of chemical fertilizers containing iron (Fe) in order to compensate for iron deficiency symptoms in apple orchards may be inevitable, but is not compatible with organic farming. Most of Iran’s temperate zone fruit orchards are located in limestone areas and iron deficiency symptoms are observed in these areas. As a result, growers use significant quantities of fertilizer containing iron that, in addition to the cost, disrupt the balance of nutritional elements in the soil. Material and methods: The study was carried out in order to find rootstock resistant to iron deficiency through the two methods of iron hunger and bicarbonate stress and to evaluate the endurance of iron deficiency-induced chlorosis in nine hybrid apples, Gami Almasi hybrid apple trees and Malling Merton 106 and their progeny were used in terms of aquiculture. Mean comparison was performed using the Duncan test at a 5% probability level using SPSS software. Results and discussion: In general, the results showed that Gami Almasi root stock was more tolerant to Fe deficiency-induced chlorosis compared to Malling Merton 106 and their progeny. Chlorophyll index, chlorophyll fluorescence, total chlorophyll content, total iron and active iron of sixth leaves from the final bud were found to have a significant difference with the Maling Merton 106 and, at times, with their progeny. The pH and Ec of the pots' drainage were influenced by the type of root stocks. Conclusion: In both methods investigated in the study of Gami Almasi, in comparison with other bases of the chlorophyll index, the visual rating of iron-deficiency, the concentration of chlorophyll in leaf from the sixth the end of the bud and the concentration of total and active iron in leaves showed better performance.